Effects of partial substitution of NaCl on myofibrillar protein properties from pearl mussel Hyriopsis cumingii muscle: Structural characteristics and aggregation behaviors - Yang, Huan-huan; Zhong, Chan; Sun, Le-chang; Li, Ya-ke; Chen, Hu; Wu, Guo-ping (Food chemistry, 2021)
•Paramyosin was the main component of MP from pearl mussel muscle.•MP showed excellent solubility and microstructure as NaCl increased to 0.6 M.•MgCl2 and CaCl2 at low replacement level could show acceptable protein properties.•The proper structure unfolding and aggregation of MP were good for its properties.•Partial substitution of NaCl could be an alternative for pearl mussel meat product. The effects of NaCl and its partial substitutes (KCl, MgCl2 and CaCl2) on solubility, structural characteristics and aggregation behaviors of myofibrillar protein (MP) from pearl mussel muscle were investigated and compared. MP at 0.6 M NaCl was beneficial to protein unfolding and showed excellent potential functional properties. When NaCl was substituted in low level, MPs also showed good solubility and ordered microstructure as well as NaCl, especially MgCl2 and CaCl2, due to the unfolding of α-helical structures and subsequently exposed tyrosine residues and hydrophobic groups. However, the obviously increased disulfide bonds and hydrophobic interactions in high substitution level indicated the excessive non-sodium salts had negative effects on molecular rearrangement, leading to irregular and overly tight of microstructure. Thus, NaCl partially substituted by KCl, MgCl2 and CaCl2 in low substitution level is promising to improve functional properties of MP in low-sodium meat products.